2018
DOI: 10.3389/fmicb.2018.01785
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Foods as a Dietary Source of Live Organisms

Abstract: The popularity of fermented foods and beverages is due to their enhanced shelf-life, safety, functionality, sensory, and nutritional properties. The latter includes the presence of bioactive molecules, vitamins, and other constituents with increased availability due to the process of fermentation. Many fermented foods also contain live microorganisms that may improve gastrointestinal health and provide other health benefits, including lowering the risk of type two diabetes and cardiovascular diseases. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
232
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(272 citation statements)
references
References 185 publications
(73 reference statements)
5
232
0
2
Order By: Relevance
“…Previous studies have demonstrated that many fermented foods are a reliable source for lactic acid bacteria, with counts of 10 5 -10 7 CFU/mL or g [32]. These include the genera found in this study.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Previous studies have demonstrated that many fermented foods are a reliable source for lactic acid bacteria, with counts of 10 5 -10 7 CFU/mL or g [32]. These include the genera found in this study.…”
Section: Discussionsupporting
confidence: 66%
“…The increase in counts after fermentation can be explained by the proliferation of bacteria in the nutrient rich cashew mix. These counts are higher than the levels generally found in fermented foods which usually contain 10 5 -10 7 CFU/mL or g of lactic acid bacteria [32]. The exception is fermented dairy products with cell counts up to 10 9 CFU/mL [32].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Due to the presence of health-promoting compounds, fermented foods are considered important components of the human diet [1]. In fact, this type of food processing not only improves the organoleptic properties of the food matrix, but it can also increase the availability of various constituents, which can exert positive effects after consumption [2]. Among these compounds, bioactive peptides are inactive in the primary structure of proteins and can be released from them by fermenting bacteria-mediated…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for dairy products, Streptococcus thermophilus, Lactobacillus delbrueckii subsp. bulgaricus and Bifidobacterium spp are usually employed [2,7]. Bioactive peptides generated from milk can originate both from whey proteins (β-lactoglobulin, α-lactalbumin, serum albumin, immunoglobulins, lactoferrin and protease-peptone fractions) and from caseins (α-, βand κ-casein) [8][9][10].…”
mentioning
confidence: 99%